1999
DOI: 10.1121/1.426169
|View full text |Cite
|
Sign up to set email alerts
|

Elastic modules modification and phonon focusing in zinc oxide

Abstract: Despite the direct observations of the acoustic waves focusing in different solids [J. P. Wolfe, Phys. Today 48, 34–40 (1995)], the properties of the phonons’ propagation and possibility of these control have not been studied in hexagonal media. To check this statement [U. V. Zubrytski, Z. Tekhn. Fiz. 67, 59–64 (1997)] and obtain striking demonstrations of drastic changes in the phonon focusing patterns at elastic properties, modification of such solids’ phonon focusing is simulated in zinc oxide grown by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been revealed that there are unusual, in comparison with the literature data, properties in STA mode to possess directions of infinite focusing in CdS. New evidences for this finding have been obtained and possibility of the control modification of the phonon fluxes in hexagonal medium has been recently demonstrated by the 3D simulation of the focusing factor in ZnO single crystals and films including ones doped with Li impurity [7, based on 2D data [8]]. To highlight the role of both elastic and piezoelectric anisotropy in the effect, it is supposed in the present paper that this can be effectively accompanied by the acoustic axes investigation method.…”
Section: Phonon Focusing Onsetmentioning
confidence: 99%
“…It has been revealed that there are unusual, in comparison with the literature data, properties in STA mode to possess directions of infinite focusing in CdS. New evidences for this finding have been obtained and possibility of the control modification of the phonon fluxes in hexagonal medium has been recently demonstrated by the 3D simulation of the focusing factor in ZnO single crystals and films including ones doped with Li impurity [7, based on 2D data [8]]. To highlight the role of both elastic and piezoelectric anisotropy in the effect, it is supposed in the present paper that this can be effectively accompanied by the acoustic axes investigation method.…”
Section: Phonon Focusing Onsetmentioning
confidence: 99%